2017
DOI: 10.1101/gad.304972.117
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genome analysis of somatic p53 mutant osteosarcomas identifies Ets2-dependent regulation of small nucleolar RNAs by mutant p53 protein

Abstract: is the most frequently mutated gene in human cancer. Many mutant p53 proteins exert oncogenic gain-of-function (GOF) properties that contribute to metastasis, but the mechanisms mediating these functions remain poorly defined in vivo. To elucidate how mutant p53 GOF drives metastasis, we developed a traceable somatic osteosarcoma mouse model that is initiated with either a single mutation (p53R172H) or loss in osteoblasts. Our study confirmed that mutant mice developed osteosarcomas with increased metastasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
3
43
1
2
Order By: Relevance
“…Whereas ETS1 knockdown had no effect on mtp53 target gene expression, ETS2 depletion reproduced changes in gene expression that occur on mtp53 depletion suggesting close relationship between mtp53 and ETS2. The observation that ETS2 interacts with various mtp53 (R175H, R248Q, R248W, R249S, R273H, R273L, and R280K) suggests that through ETS2 binding, different mtp53 proteins reveal oncogenic potential through common mechanisms consistent with the recent MD Anderson study (172). …”
Section: Ets1 and Ets2supporting
confidence: 83%
See 4 more Smart Citations
“…Whereas ETS1 knockdown had no effect on mtp53 target gene expression, ETS2 depletion reproduced changes in gene expression that occur on mtp53 depletion suggesting close relationship between mtp53 and ETS2. The observation that ETS2 interacts with various mtp53 (R175H, R248Q, R248W, R249S, R273H, R273L, and R280K) suggests that through ETS2 binding, different mtp53 proteins reveal oncogenic potential through common mechanisms consistent with the recent MD Anderson study (172). …”
Section: Ets1 and Ets2supporting
confidence: 83%
“…Very recently, the Lozano’s group elucidated how GOF mtp53 drove cancer metastasis by developing a traceable osteosarcoma mouse model (172). They showed that mtp 53 mice developed osteosarcomas with increased metastasis as compared with p53 -null mice.…”
Section: Ets1 and Ets2mentioning
confidence: 99%
See 3 more Smart Citations